Editorial for Special Issue: Metaproteomics - Jana Seifert; Thilo Muth (Proteomes, 2019)
As the proteome-level counterpart of metagenomics, metaproteomics extends conventional single-organism proteomics and allows researchers to characterize the entire protein complement of complex microbiomes on a large scale [...]